1993
DOI: 10.2105/ajph.83.7.983
|View full text |Cite
|
Sign up to set email alerts
|

Early menopause, number of reproductive years, and bone mineral density in postmenopausal women.

Abstract: OBJECTIVES. Previous studies have reported positive associations of age at menopause with bone density and inverse associations of age at menarche with bone density. This study examined the relationships of early age at menopause and number of reproductive years (defined as age at menopause minus age at menarche) with bone density in postmenopausal women. METHODS. The subjects were 555 women aged 60 to 89 years who had had either natural menopause (n = 391) or hysterectomy with bilateral oophorectomy (n = 164)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0
6

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(92 citation statements)
references
References 17 publications
3
83
0
6
Order By: Relevance
“…12 Premenopausal estrogen maintains bone density in women and premature loss of this estrogen due to accelerated menopause elevates risk for osteoporosis and bone fractures. 13,14 Although hormone replacement therapy can correct this, it may also place women at increased risk of coronary heart disease, stroke, pulmonary embolism, and invasive breast cancer. 15 Overall, accelerated reproductive senescence due to depletion of ovarian reserves is associated with reduced quality of life and decreased lifespan.…”
Section: Introduction: Infertility and Its Consequencesmentioning
confidence: 99%
“…12 Premenopausal estrogen maintains bone density in women and premature loss of this estrogen due to accelerated menopause elevates risk for osteoporosis and bone fractures. 13,14 Although hormone replacement therapy can correct this, it may also place women at increased risk of coronary heart disease, stroke, pulmonary embolism, and invasive breast cancer. 15 Overall, accelerated reproductive senescence due to depletion of ovarian reserves is associated with reduced quality of life and decreased lifespan.…”
Section: Introduction: Infertility and Its Consequencesmentioning
confidence: 99%
“…In the study of 555 women aged 60 to 89 years age at menopause and number of reproductive years had positive associations with bone mineral density of radius, hip and spine, and total number of reproductive years explained more of variance in BMD than did either age at menarche or age at menopause [27]. In our study we did not note an influence of menstrual years on QUS parameters, but in early postmenopausal women menstrual years in regard to lifetime significantly improved value of SOS.…”
Section: Discussionmentioning
confidence: 92%
“…In several studies the influence of different factors on bone densitometry measurements were performed [27,28,30,31,34,36,38]. In the study of 555 women aged 60 to 89 years age at menopause and number of reproductive years had positive associations with bone mineral density of radius, hip and spine, and total number of reproductive years explained more of variance in BMD than did either age at menarche or age at menopause [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With varying consistency studies found an earlier menopause to be associated with low education or social status [6,9,12,16,21,22]. Further, an early menopause was found for ischemia [23][24][25] and osteoporosis [26,27].…”
Section: Introductionmentioning
confidence: 99%